Impact of Contextual Factors on the Attendance and Role in the Evidence-Based Chronic Disease Prevention Programs Among Primary Care Practitioners in Shanghai, China - Liu, Xin; Gong, Xin; Gao, Xiang; Wang, Zhaoxin; Lu, Sheng; Chen, Chen; Jin, Hua; Chen, Ning; Yang, Yan; Cai, Meiyu; Shi, Jianwei (Frontiers in Public Health, 2022)
Background: The implementation of evidence-based approaches by general practitioners (GPs) is new in the primary care setting, and few quantitative studies have evaluated the impact of contextual factors on the attendance of these approaches. Methods: In total, 892 GPs from 75 community healthcare centres (CHCs) in Shanghai completed our survey. We used logistic regression to analyse factors affecting the number of evidence-based chronic disease programmes attended by GPs and whether they had held the lead position in such a programme. Results: A total of 346 (38.8%) of the practitioners had never participated in any evidence-based chronic disease prevention (EBCDP) programme. The EBCDP interventions in which the GPs participated were predominantly related to hypertension, diabetes, and cardiovascular disease. However, the proportion of GPs in the lead role was relatively low, between 0.8% (programmes involving prevention and control of asthma) and 5.0% (diabetes). Organizational factors and area were significantly associated with GPs’ evidence-based practices, while monthly income and department were most significantly related to GPs having the lead role in a programme. The results indicated that GPs who had taken the lead position had higher scores for policy and economic impeding factors. GPs who were male, had a higher income, and worked in prevention and healthcare departments and urban areas were more likely to take the lead position. Conclusion: Evidence-based programmes for chronic diseases should be extended to different types of diseases. Personal, organizational, political and economic factors as well as the factors of female sex, lower income, department type and suburban area environment should be considered to facilitate the translation of evidence to practice.